Innovative Approaches in Music Pedagogy: Modern Methods of Teaching and Developing Musical Skills - Karimova, M. M. (Researchparks Publishing, 2023)
In the realm of musical pedagogy, the evolution of innovative approaches has redefined teaching methodologies, reshaping the acquisition and honing of musical skills. This article explores contemporary methods employed in music education, delving into their impact on skill development and learning outcomes.